2013
DOI: 10.1007/s11999-013-2875-0
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus aureus Screening and Decolonization in Orthopaedic Surgery and Reduction of Surgical Site Infections

Abstract: Background Staphylococcus aureus is the most common organism responsible for orthopaedic surgical site infections (SSIs). Patients who are carriers for methicillin-sensitive

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
101
2
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(106 citation statements)
references
References 56 publications
(244 reference statements)
1
101
2
2
Order By: Relevance
“…Chen and colleagues included 19 studies related to orthopaedic surgery in their review -many with questionable methodologies. The authors concluded that all of the studies showed a reduction in surgical site infections or wound complications by instituting S aureus screening and decolonization [3]. We disagree with this analysis.…”
Section: To the Editormentioning
confidence: 84%
See 2 more Smart Citations
“…Chen and colleagues included 19 studies related to orthopaedic surgery in their review -many with questionable methodologies. The authors concluded that all of the studies showed a reduction in surgical site infections or wound complications by instituting S aureus screening and decolonization [3]. We disagree with this analysis.…”
Section: To the Editormentioning
confidence: 84%
“…In their study, the authors studied whether Staphylococcus aureus screening and decolonization strategy reduce surgical site infections in orthopaedic surgery [3]. This question is of great concern as S aureus is a major risk factor for surgical site infections, notably in orthopaedic surgery [2,6].…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation
“…Culture swabs of the anterior nares can identify patients who are colonized with MRSA even though they may show no signs or symptoms of infection. 2 MRSA and other microbes have been cultured from bath basins in ICUs, 3 which may contribute to colonization of the patient's skin and lead to secondary contamination at other sites. 4 Reduction and elimination of hospital-acquired infections requires a multipronged approach.…”
mentioning
confidence: 99%
“…4,[11][12][13]16,17 Bathing with CHG also reduces MRSA skin colonization in known MRSA carrier patients during their treatment. [18][19][20][21] Several studies showed that bathing with CHG and nasal administration of mupirocin reduce the risk of infections, 2,22 and CHG bathing alone specifically reduces the risk of central catheter-associated bloodstream infections in ICU patients 4,[23][24][25][26] and long-term acute care patients. 27 Two studies 24,28 demonstrated that CHG bathing reduced the rate of blood culture contamination.…”
mentioning
confidence: 99%